Empowerment of Cash-for-Work Program in Routine Bridge Maintenance Projects - Anwar, M. Syaiful; Adiansyah, Nur (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This study examines the implementation of the Cash-for-Work (CFW) program in routine bridge maintenance projects along the Surabaya-Gresik-Sadang road section. The primary objective of the program is to provide employment opportunities for individuals affected by the COVID-19 pandemic, particularly unemployed, low-income, and displaced workers. The program aims to contribute to national economic recovery by enhancing the purchasing power of the local community while ensuring the maintenance and improvement of public infrastructure. Through a participatory action research approach, this project engaged the local population in community-driven maintenance work, thus reducing unemployment and promoting sustainable economic development. The findings highlight the program's success in creating local employment, improving infrastructure, and alleviating the economic challenges faced by the community due to the pandemic